The Potential of Fermented Local Food Consumption on the Gut Microbiota Status of Adolescents - Safridha Kemala Putri; Nurhaedah Nurhaedah (International Journal of Health Sciences, 2026)
ABSTRACT Local fermented foods are a source of natural probiotics that have the potential to provide benefits for digestive health, particularly in maintaining the balance of the gut microbiota. Consumption of fermented foods such as tempeh, fermented cassava, and traditional yogurt is known to contain microorganisms that can support the growth of beneficial bacteria in the digestive tract. This study aims to analyze the potential effect of local fermented food consumption on the gut microbiota status of adolescents. The study used an analytical design with a cross-sectional approach. The study sample consisted of 90 adolescents selected using a purposive sampling technique. Data were collected through a questionnaire regarding the frequency of fermented food consumption and examination of digestive health indicators. Data were analyzed using the chi-square test. The results showed that adolescents who regularly consumed fermented foods had better gut microbiota status than those who rarely consumed fermented foods. The statistical test showed a p- value of 0.015 (p < 0.05). It was concluded that consumption of local fermented foods has the potential to improve gut microbiota balance in adolescents. Keywords: Fermented Foods, Gut Microbiota, Probiotics, Adolescents